2008
DOI: 10.1016/j.biopsych.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A Rhesus Monkey Model of Self-Injury: Effects of Relocation Stress on Behavior and Neuroendocrine Function

Abstract: Our results indicate that relocation is a significant stressor for rhesus macaques and that this stressor triggers an increase in self-biting behavior as well as sleep disturbance in monkeys previously identified as suffering from SIB. These findings suggest that life stresses may similarly exacerbate SIB in humans with this disorder. The HPA axis results underscore the potential role of CBG in regulating long-term neuroendocrine responses to major stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 50 publications
8
124
0
1
Order By: Relevance
“…The hair sampling technique has been available in rhesus macaques (36,34,37) and is a unique tool for assessing longterm changes in HPA system activity (36). In fact, hair cortisol represents the cumulative secretion of cortisol over months and is not affected by circadian rhythms or other factors.…”
Section: Xiaolimentioning
confidence: 99%
“…The hair sampling technique has been available in rhesus macaques (36,34,37) and is a unique tool for assessing longterm changes in HPA system activity (36). In fact, hair cortisol represents the cumulative secretion of cortisol over months and is not affected by circadian rhythms or other factors.…”
Section: Xiaolimentioning
confidence: 99%
“…The extraction and assay procedures were validated in part by demonstrating that serial dilutions of extracts from monkey hair samples yielded EIA readings that closely paralleled the readings obtained from authentic CORT standards. We then showed that hair CORT (in addition to plasma and salivary CORT) was sensitive to the major life stressor of an administratively mandated relocation of the monkeys to new housing quarters 4,5 . The present paper provides a detailed account of the methods used routinely in our laboratory to process human and monkey hair samples and to extract and analyze CORT from such samples.…”
Section: Introductionmentioning
confidence: 97%
“…Cortisol and corticosterone are the endogenous glucocorticoids in humans and rodents, respectively (Terao and Katayama 2016), and the major glucocorticoid hormone in birds is corticosterone (Holmes and Phillips 1976). Cortisol has long been considered to be a reliable physiological measure of the stress response in domestic mammals such as guinea pigs (Kunzl et al 2003), pigs (Turner et al 2005), sheep (Smith and Dobson 2002), goats (Aoyama et al 2008), cows (Christison and Johnson 1972) and horses (Visser et al 2008) and in wild mammals, e.g., Antechinus (Bradley et al 1980), Macaca (Davenport et al 2008), Odocoileius (Millspaugh et al 2002), Peromyscus (Hayssen et al 2002), Procavia , Puma (Bonier et al 2004), Saimiri (Lyons et al 1995) and Spermophilus (Mateo 2008;Delehanty and Boonstra 2009). The stress response in vertebrates, mediated by the HPA axis, involves the release of adrenocorticotrophic hormone (ACTH) into the blood stream, which in turn acts on the adrenal cortex to activate the secretion of glucocorticoids (Tsigos and Chrousos 2002).…”
Section: Stress Hormonesmentioning
confidence: 99%